Auscultación de pavimento para el inventario de la malla vial de Antioquia en las subregiones Norte y Bajo Cauca. (2011)
This report assessed the functional condition of the pavement on secondary roads of North and sub-Bajo Cauca Antioquia department. The functional behavior of a pavement includes several parameters that are responsible for providing a safe and comfortable surface for users, among which are the regularity, slip resistance and damage, as this does not involve the structural capacity of pavement. Hese parameters are evaluated with high performance teams to accomplish the data quickly and continuously. This work focuses on assessing the parameter regularity, characteristic perceived by the user through the sense of more or less comfort, which was assessed ROMDOS team which consists of an integrated digital sensor, which is responsible for registering vertical displacement data between the vehicle and the pavement every 50 m in a systematic way. And the damage present in the pavement structure, which was conducted survey and record the respective boxes in the field that specified the type of damage, floor, severity and extent. Gravity: it presents the levels of severity are: Low, medium and high. Extension: This is the length or area. Then be processed using the methodology vizier.